ANALISIS PERILAKU FOOD WASTE DI RESTORAN SEDERHANA DI KOTA BATAM MENURUT SUDUT PANDANG THEORY OF PLANNED BEHAVIOR - Hendra Syaiful (Bajang Institute, 2025)
This study aims to analyze food waste behavior in restaurants through the lens of the Theory of Planned Behavior (TPB). The analysis is based on a literature review to explore the factors influencing food waste behavior in restaurants, including consumer attitudes, social norms, and perceptions of behavioral control. The research method employed is a literature study, reviewing various previous studies relevant to food waste in restaurants and the application of TPB in understanding consumer behavior. The findings indicate that food waste behavior in restaurants is influenced by positive attitudes, social norms, and perceptions of behavioral control. Other factors affecting food waste behavior in restaurants include cultural influences, eating habits, and restaurant management policies. Based on these findings, it can be concluded that TPB can serve as a framework for understanding food waste behavior in restaurants, which can subsequently form the basis for the development of policies aimed at reducing food waste in restaurants, with a focus on increasing consumer awareness to encourage more environmentally responsible behavior.